(untitled) (Metallurgy and Foundry Engineering, 2006)
This paper deals with the issue of numerical modelling of the piercing process of thick-walled tube shell in two-rolls skew rolling mill, which is equipped with guiding devices of Diescher type. After a short characteristic of the process, the worked out numerical model of this process is described. The numerical model considers e.g. thermal phenomena taking place in the metal during forming. Moreover, in this model tools were assumed as rigid bodies apart from the piercing plug which could be deformed in the elastic range. Applying the worked out FEM model, simulations of the piercing process in the skew rolling mill were made. The results of calculations were presented in the form of maps of: strains, stresses, temperatures and surface pressures.